Amine protection by in situ formation of choline chloride-based deep eutectic solvents. Issue 8 (3rd April 2023) - Nardi, Monica; De Luca, Giuseppina; Novelli, Paolo; Oliverio, Manuela; Romano, Salvatore; Procopio, Antonio
Abstract : Protection of amine groups by amide formation is still among the preferred strategies for multifunctional molecular synthesis despite its waste production, especially the enormous quantities of organic solvents used. Abstract : Protection of amine groups by amide formation is still among the preferred strategies for multifunctional molecular synthesis despite its waste production, especially the enormous quantities of organic solvents used. In this study, we present a fast, cheap and eco-friendly method for amine group protection involving amide bond formation using choline chloride as a hydrogen bond acceptor and the starting amine as a hydrogen bond donor through the generation of " in situ " amine-based deep eutectic solvents. This novel approach avoids the use of toxic solvents, both during reaction and the work-up phase, thus representing a sustainable alternative to classic amine protection procedures.